Microsoft Project 2016 Step by Step - Carl Chatfield; Timothy Johnson (USA Microsoft Press, 2016)
This is learning made easy. Get more done quickly with Project 2016. Jump in wherever you need answers-brisk lessons and colorful screenshots show you exactly what to do, step by step. Quickly start a new plan, build task lists, and assign resources Share your plan and track your progress Capture and fine-tune work and cost details Use Gantt charts and other views and reports to visualize project schedules Share resources across multiple plans and consolidate projects Master project management best practices while you learn Project Look up just the tasks and lessons you need.
Keywords: Textbooks; Nonfiction; Project management; Planning and Control of Projects (BIN2051-N)